Tanreqing Inhibits LPS-Induced Acute Lung Injury In Vivo and In Vitro Through Downregulating STING Signaling Pathway - He, Yu-Qiong; Zhou, Can-Can; Deng, Jiu-Ling; Wang, Liang; Chen, Wan-Sheng (Frontiers in Pharmacology, 2021)
Acute lung injury (ALI) as a common life-threatening lung disease is mostly associated with serious inflammatory responses and oxidative stress. Tanreqing injection (TRQ), a Chinese patent medicine, is clinically used for respiratory-related diseases, including COVID-19 in China. However, the effects of TRQ on ALI and the action mechanism are still unclear. Recently, STING as a cytoplasmic DNA sensor has been found to be associated with the progress of ALI. In this study, we sought to investigate whether TRQ can inhibit LPS-induced ALI in vivo and in vitro and evaluate the involvement of STING signaling pathway. The results showed that TRQ significantly inhibited LPS-induced lung histological change, lung edema and inflammatory cell infiltration. Moreover, TRQ markedly reduced inflammatory mediators release (TNF-α, IL-6, IL-1β, and IFN-β) in ALI mice and LPS-stimulated RAW 264.7 cells. Furthermore, TRQ also alleviated oxidative stress in LPS-induced ALI mice and RAW 264.7 cells demonstrated by increased SOD and GSH activities as well as decreased 4-HNE, MDA, LDH, and ROS activities. In addition, we further found that TRQ significantly prevented cGAS, STING, P-TBK, P-P65, P-IRF3, and P-IκBα expression in ALI mice. And the in vitro results also confirmed that TRQ could inhibited mtDNA release and suppressed STING mediated signaling pathway. Importantly, the use of DMXAA, which is a commonly defined STING agonist, dramatically abolished the protective effects of TRQ in LPS-stimulated mice and RAW 264.7 cells. Taken together, the present study indicated that TRQ alleviated LPS-induced ALI and inhibited inflammatory responses and oxidative stress through STING signaling pathway.